Rapid recovery after oxford unicompartmental arthroplasty through a short incision. - Price, A; Webb, J; Topf, H; Dodd, C; Goodfellow, J; Murray, D (2001)
Forty Oxford medial unicompartmental arthroplasties (UCAs) were performed through a short incision medial to the patellar tendon, without dislocation of the patella, using updated instruments (Oxford Knee Phase III, Biomet Ltd., Bridgend, UK). The rate of recovery of these knees (measured by the time taken to achieve straight-leg raising, 70 degrees of flexion, and independent stair climbing) was compared with that of 20 Oxford UCAs performed through an open approach with dislocation of the patella. Both groups were compared with 40 AGC (Biomet) total knee arthroplasties performed for osteoarthritis during the same time period. The average rate of recovery after the short-incision UCA was twice as fast as after open UCA and 3 times as fast as after total knee arthroplasty. Accuracy of implantation, assessed from 11 variables seen on fluoroscopically centered postoperative radiographs, was the same after UCA by the short-incision approach as after the open approach, suggesting that the short-term advantage of increased speed of recovery was gained without affecting the long-term results. We now employ the short incision with the phase III instruments for all UCAs.